2022
DOI: 10.34172/aim.2022.18
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence Rates of Breast and Gynecological Cancers in Asia from 1998–2012: An Ecological Study

Abstract: Background: There is limited evidence on the epidemiology and time trend analysis of incidence rates of gynecological cancer in Asia as a whole. We conducted this study to demonstrate breast and gynecological cancers incidence and trends in selected Asian populations. Method: We conducted this ecological study using cancer and population data from cancer incidence in five continents (CI5). We extracted the data of breast, uterine, cervix and ovary cancers in selected Asian populations from 1998 to 2012 from CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, patients should be screened for ovarian cancer after the first diagnosis of breast cancer, even after 10 years (Bergfeldt et al ., 2002; Chen et al ., 2020a). What’s more, more than half of cervical cancers occur in women who are inadequately screened in the USA and introduction of screening to populations naive to screening reduces cervical cancer rates by 60–90% within 3 years of implementation (Moyer, 2012; Eslahi et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients should be screened for ovarian cancer after the first diagnosis of breast cancer, even after 10 years (Bergfeldt et al ., 2002; Chen et al ., 2020a). What’s more, more than half of cervical cancers occur in women who are inadequately screened in the USA and introduction of screening to populations naive to screening reduces cervical cancer rates by 60–90% within 3 years of implementation (Moyer, 2012; Eslahi et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of endometrial carcinoma (EC) is increasing year by year. EC is the second most common cancer of the female reproductive system, especially in Asia ( 1 , 2 ). Existing research has shown that the prognosis of patients with EC worsens significantly as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%